2021
DOI: 10.1038/s41467-021-27404-3
|View full text |Cite
|
Sign up to set email alerts
|

Reductive inactivation of the hemiaminal pharmacophore for resistance against tetrahydroisoquinoline antibiotics

Abstract: Antibiotic resistance is becoming one of the major crises, among which hydrolysis reaction is widely employed by bacteria to destroy the reactive pharmacophore. Correspondingly, antibiotic producer has canonically co-evolved this approach with the biosynthetic capability for self-resistance. Here we discover a self-defense strategy featuring with reductive inactivation of hemiaminal pharmacophore by short-chain dehydrogenases/reductases (SDRs) NapW and homW, which are integrated with the naphthyridinomycin bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…The results further indicated that Q 12 -CNHBP was less likely to induce bacteria to develop resistance compared to conventional antibiotics that target specific intracellular materials. 55–58…”
Section: Resultsmentioning
confidence: 99%
“…The results further indicated that Q 12 -CNHBP was less likely to induce bacteria to develop resistance compared to conventional antibiotics that target specific intracellular materials. 55–58…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Tang and coworkers reported an interesting mechanism of self-resistance when the bacterial host produced lemonomycin and naphthyridinomycin [21]. In the fermentation of S. candidus LL-AP191, 16-dehydroxy-LMM (1a), was identified instead of LMM (Scheme 4).…”
Section: Current Status Of Biosynthesismentioning
confidence: 99%
“…The self-resistance strategy poses a challenge to develop a sophisticated biosynthetic pathway to reharvest such potent antibiotics in engineered biosynthetic machinery [22]. Very recently, Tang and coworkers reported an interesting mechanism of self-resistance when the bacterial host produced lemonomycin and naphthyridinomycin [21]. In the fermentation of S. candidus LL-AP191, 16-dehydroxy-LMM (1a), was identified instead of LMM (Scheme 4).…”
Section: Current Status Of Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a FAD-binding oxidoreductase NapU encoded in BGC of NDM was reported to activate and inactivate the matured prodrug by extracellular oxidation conferring self-protection [ 113 ]. Recently, a short-chain dehydrogenase NapW mediated the reduction of the hemiaminal pharmacophore, implicating another level of the self-resistance mechanism of the tetrahydroisoquinoline family [ 114 ].…”
Section: Dna-alkylating Natural Products With Imine As Warheadsmentioning
confidence: 99%